1990
DOI: 10.3133/pp1403e
|View full text |Cite
|
Sign up to set email alerts
|

Hydrology of the Floridan aquifer system in east-central Florida

Abstract: REGIONAL AQUIFER-SYSTEM ANALYSIS-FLORIDAN AQUIFER SYSTEM Floridan pumpage tends to induce leakage from the overlying surficial aquifer system and to reduce upward discharge to it, thereby lowering the water table. Hydrologic analysis of Floridan aquifer system discharge led to the discovery and measurement of two hitherto undocumented springs. PREVIOUS INVESTIGATIONS Many investigators have studied the Floridan aquifer system groundwater resource in east-central Florida. Among the more notable pioneer studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
2

Year Published

2002
2002
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(86 citation statements)
references
References 10 publications
3
80
2
Order By: Relevance
“…This suggested that although there may be some localized temporary perching of water, the lack of continuity in these properties allows the infiltrated water to quickly reach the groundwater table, which is near the surface most times of the year. These results also support previous studies on the hydrogeology of northeast Florida region, which reported that the thickness of the surficial aquifer in the area may range from 9 m to 26 m from the surface (Healy, 1982), which at the bottom was separated from the deeper Floridan Aquifer system by a confining unit (Tibbals, 1990;Durden 1997;Brown et al, 1986;Krause and Randolph, 1989). According to Healy (1982), the water table elevations in the surficial aquifer are the reflections of the landscape configuration, and in low flat areas, the water table stands commonly at or within a few feet of the land surface.…”
Section: Implications To Water Managementsupporting
confidence: 90%
“…This suggested that although there may be some localized temporary perching of water, the lack of continuity in these properties allows the infiltrated water to quickly reach the groundwater table, which is near the surface most times of the year. These results also support previous studies on the hydrogeology of northeast Florida region, which reported that the thickness of the surficial aquifer in the area may range from 9 m to 26 m from the surface (Healy, 1982), which at the bottom was separated from the deeper Floridan Aquifer system by a confining unit (Tibbals, 1990;Durden 1997;Brown et al, 1986;Krause and Randolph, 1989). According to Healy (1982), the water table elevations in the surficial aquifer are the reflections of the landscape configuration, and in low flat areas, the water table stands commonly at or within a few feet of the land surface.…”
Section: Implications To Water Managementsupporting
confidence: 90%
“…Figure 9-7 shows a map of the spatial distribution of the estimated recharge field. The recharge estimates range from -10.2 cm/yr to 11.3 cm/yr, and are within the range of published recharge-discharge values (Tibbals 1990). The area of known spring discharge is clearly identified by the large negative recharge values predicted in the northern portion of the study area.…”
Section: Application Of the Extended Kalman Filter To Field-scale Submentioning
confidence: 64%
“…Figure 9-3 shows that although the general trend for groundwater movement is approximately from southwest to northeast, there is significant spatial variability around this mean behavior. The pronounced dip in the 5 m to 10 m head contours in the northern portion of the study region is evidence of significant local discharge from seven major springs mapped in the area (Tibbals 1990). Figure 9-4 shows histograms of the estimation errors obtained using head and transmissivity measurements for estimating the head distribution (bivariate conditioning) compared with estimation errors obtained when only head measurements were used (univariate conditioning).…”
Section: Application Of the Extended Kalman Filter To Field-scale Submentioning
confidence: 96%
See 2 more Smart Citations